Flood Exposure and Child Malnutrition in Low- and Middle-Income Countries: A Systematic Literature Review of Stunting, Wasting, and Underweight Among Children Under Five - Oni Safriani (Universitas Muhammadiyah Semarang, 2026)
Flood disasters are recurrent hydrometeorological events that disproportionately affect vulnerable populations, particularly under-five children. Post-flood conditions disrupt food systems, sanitation infrastructure, household income, and access to health services, increasing the risk of child malnutrition. This study aims to systematically synthesize evidence on the impact of floods on the nutritional status of under-five children. A Systematic Literature Review (SLR) was conducted using the Scopus database. From 1,495 identified articles, a multi-stage screening process (2021–2026 publications, research articles, final stage, accessible documents) resulted in 22 eligible studies for in-depth analysis. The findings reveal consistent associations between flood exposure and increased risks of stunting, wasting, and underweight. Stunting appears as the most persistent long-term consequence, especially among children under two years old, whereas wasting and underweight are more sensitive to short-term post-disaster shocks. The impacts are mediated by household food insecurity, infectious diseases, poor water and sanitation conditions, and socio-economic vulnerability. Floods therefore function not only as environmental shocks but also as structural determinants of child malnutrition, highlighting the need for integrated nutrition-sensitive disaster risk reduction strategies. Keyword : flood disaster; child malnutrition; stunting; wasting; underweight; food security